2013
DOI: 10.1007/s11427-013-4447-7
|View full text |Cite
|
Sign up to set email alerts
|

Advances in cell lineage reprogramming

Abstract: As a milestone breakthrough of stem cell and regenerative medicine in recent years, somatic cell reprogramming has opened up new applications of regenerative medicine by breaking through the ethical shackles of embryonic stem cells. However, induced pluripotent stem (iPS) cells are prepared with a complicated protocol that results in a low reprogramming rate. To obtain differentiated target cells, iPS cells and embryonic stem cells still need to be induced using step-by-step procedures. The safety of induced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Whereas "program" in biology stands for a series of developmental and differentiation processes that are orderly arranged in the life cycle of an organism, "reprogram" is the reversal of programming, which refers to the erasure and remodeling of the functional state of the genome, resulting in the conversion of a differentiated cell to an immature cell (pluripotent) or the transit directly from one lineage to another (lineage reprogramming) [61]. Although it has been studied more than 50 years and remarkable breakthroughs were obtained [62][63][64], only in recent years has cellular reprogramming attracted unprecedented attention, especially after Yamanaka and colleagues [65,66] reported that fibroblasts can be induced into pluripotent stem cells (iPS cells) by the forced expression of four transcription factors (OCT4, KLF4, MYC and SOX2, which are collectively called OKMS).…”
Section: Reprogramming the Somatic Cells Into Pluripotent Cells Or Otmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas "program" in biology stands for a series of developmental and differentiation processes that are orderly arranged in the life cycle of an organism, "reprogram" is the reversal of programming, which refers to the erasure and remodeling of the functional state of the genome, resulting in the conversion of a differentiated cell to an immature cell (pluripotent) or the transit directly from one lineage to another (lineage reprogramming) [61]. Although it has been studied more than 50 years and remarkable breakthroughs were obtained [62][63][64], only in recent years has cellular reprogramming attracted unprecedented attention, especially after Yamanaka and colleagues [65,66] reported that fibroblasts can be induced into pluripotent stem cells (iPS cells) by the forced expression of four transcription factors (OCT4, KLF4, MYC and SOX2, which are collectively called OKMS).…”
Section: Reprogramming the Somatic Cells Into Pluripotent Cells Or Otmentioning
confidence: 99%
“…Remarkably, an important breakthrough was made in 2010, when, for the first time, transdifferentiation across germ layers-conversion of mouse fibroblasts (mesoderm) to neurons (ectoderm) was achieved [108]. Similar to that in the reprogramming of pluripotent cells, transcription factors are widely employed in the induction of transdifferentiation and the number of successful studies is constantly increasing [61,115]. Interestingly, two groups of tissue-specific miRNAs have been shown to accomplish this mission as excellently as transcription factors [116,117].…”
Section: Reprogramming the Somatic Cells Into Pluripotent Cells Or Otmentioning
confidence: 99%